Shoulder joint velocity during fastball pitching in baseball - Gasparutto, X.; van der Graaff, E.; van der Helm, F.; Veeger, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess the rotation and translation velocity of the shoulder complex during fastball pitching in baseball. 8 pitchers from the Dutch AAA team performed each 3 fastball pitches. Their motion was recorded by an opto-electronic device. Kinematic computation was performed using the quaternion algebra. The results showed that the endo-rotation, depression and backward rotation velocity of the humerus at ball release are initiated by a translation of the scapular girdle in the forward and upward direction before ball release.